2003
DOI: 10.1359/jbmr.2003.18.11.1947
|View full text |Cite
|
Sign up to set email alerts
|

BMD at Multiple Sites and Risk of Fracture of Multiple Types: Long-Term Results From the Study of Osteoporotic Fractures

Abstract: In a large cohort of U.S. women aged 65 and older, we report the relationships of BMD measured at several sites, and subsequent fracture risk at multiple sites over >8 years of follow-up. Although we found almost all fracture types to be related to low BMD, the overall proportion of fractures attributable to low BMD is modest.Introduction: Although several studies have reported the relationship between bone mineral density (BMD) and subsequent fracture risk, most have been limited by short follow-up time, BMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
484
3
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 895 publications
(539 citation statements)
references
References 42 publications
23
484
3
14
Order By: Relevance
“…Importantly, among the patients with vertebral fractures, 29 -35.8% had normal BMD (24,50). This finding is in line with results from studies in the general population reporting that the proportion of fractures attributable to osteoporosis is only 10 -44% (51).These data point to the limited value of BMD measurement in the assessment of future fracture risk.…”
Section: Fractures and Osteoporosis In Slesupporting
confidence: 82%
“…Importantly, among the patients with vertebral fractures, 29 -35.8% had normal BMD (24,50). This finding is in line with results from studies in the general population reporting that the proportion of fractures attributable to osteoporosis is only 10 -44% (51).These data point to the limited value of BMD measurement in the assessment of future fracture risk.…”
Section: Fractures and Osteoporosis In Slesupporting
confidence: 82%
“…The National Osteoporosis Risk Assessment (NORA) study reported similar results for heel, forearm and finger BMD [13]. These findings were confirmed by the 10-year data of the Study of Osteoporotic Fractures (SOF), which reported RR values around 1.4 for six different BMD measurement sites (distal and proximal radius, heel, spine, total hip and femoral neck) [14]. In the present study, the adjusted HR for any clinical fracture attributed to a decrease of 1 SD in BMD was 1.5 for T-DIA and 1.8 for T-EPI.…”
Section: Discussionmentioning
confidence: 60%
“…Fracture risk is best predicted by site-matched measurement of areal bone mineral density (aBMD) with dual-energy X-ray absorptiometry [2]. However, aBMD alone is not sufficient to account for bone strength [3,4]. The development of a quantitative ultrasound (QUS) hip scanner [5,6] aims at providing an alternative to aBMD measurements.…”
Section: Introductionmentioning
confidence: 99%